The effect of bone morphogenetic protein 2 composite materials combined with cannulated screws in treatment of acute displaced femoral neck fractures - Gao, Hongwei (Medicine (Baltimore), 2020)
The risk of avascular necrosis (AVN) and nonunion after treatment of displaced femoral neck fractures is increased in patients aged <60 years. Therefore we established a new protocol for closed reduction and internal fixation (CRIF) using cannulated screws combined with bone morphogenetic protein 2 (BMP-2) composite materials to treat acute femoral neck fractures. This study enrolled 78 patients with acute femoral neck fractures between April 2014 and September 2016. We treated 46 patients with a mean age of 43.8 years in study group. These patients were treated by CRIF combined with BMP-2 composite materials. In control group, there were 32 patients with a mean age of 42.09 years. The patients were treated by CRIF without BMP-2. The duration between presentation and surgery, operative time, Harris score and complications were recorded. In study group, 43 patients were followed up with an average of 31.3 months. One patient suffered nonunion and three patients presented AVN. In control group, 28 patients were followed up with an average of 32.3 months, the rate of AVN and fracture nonunion were 25% (7/28) and 21.4% (6/28) respectively, significantly higher than those in study group (P < .05). Acute displaced femoral neck fractures can be treated with CRIF and BMP-2 composite materials in a minimally invasive manner. This technique was reproducible and had fewer complications.